2003
DOI: 10.1016/s1074-7613(03)00300-5
|View full text |Cite
|
Sign up to set email alerts
|

The IL-27R (WSX-1) Is Required to Suppress T Cell Hyperactivity during Infection

Abstract: Although recent studies have described IL-27 and its receptor, WSX-1, as promoters of Th1 differentiation in naive CD4+ T cells, the data presented here indicate that signaling through this receptor is involved in limiting the intensity and duration of T cell activity. When WSX-1-deficient mice are infected with the intracellular pathogen Toxoplasma gondii, they establish protective T cell responses, characterized by production of inflammatory cytokines and control of parasite replication. However, infected WS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
509
4
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 440 publications
(548 citation statements)
references
References 43 publications
(2 reference statements)
31
509
4
4
Order By: Relevance
“…Lack of IL-12R␤1 (also a subunit for the IL-23R complex) resulted in reduced IL-1 production and inflammation in coxsackie virus B3-induced myocarditis in mice (39). Our findings of overproduction of proinflammatory cytokines by NKT cells in Con A-treated WSX-1-deficient mice confirm the recently proposed novel role for WSX-1 as an inhibitory regulator of inflammation and cytokine production (25,26). With further identifications of FIGURE 6.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Lack of IL-12R␤1 (also a subunit for the IL-23R complex) resulted in reduced IL-1 production and inflammation in coxsackie virus B3-induced myocarditis in mice (39). Our findings of overproduction of proinflammatory cytokines by NKT cells in Con A-treated WSX-1-deficient mice confirm the recently proposed novel role for WSX-1 as an inhibitory regulator of inflammation and cytokine production (25,26). With further identifications of FIGURE 6.…”
Section: Discussionsupporting
confidence: 84%
“…We also reported that IL-27 induce STAT1 phosphorylation downstream of WSX-1 and also that IL-27 causes IL-12 responsiveness to naive CD4 ϩ T cells by induction of IL-12R␤2 (23). More recently, we have reported that in the absence of WSX-1, both CD4 ϩ T cells and NK1.1 ϩ CD3 ϩ NKT cells overproduced several inflammatory cytokines during Toxoplasma gondii or Trypanosoma cruzi infection (25,26), demonstrating a new role for WSX-1 as an inhibitory regulator of cell activation and cytokine production. Thus, although the role of IL-27/WSX-1 signaling in the differentiation of naive CD4 ϩ T cells into Th1 population has become clearer, functions of WSX-1 in various milieus have not been fully understood.…”
Section: Hyperproduction Of Proinflammatory Cytokines By Wsx-1-deficimentioning
confidence: 84%
See 1 more Smart Citation
“…The cytokine receptor WSX-1/T cell cytokine receptor, which is homologous to the IL-12R␤2 subunit, and a commonly used cytokine receptor for the IL-6 family, gp130, constitute a functional signal-transducing receptor for IL-27 (1,2). IL-27 activates JAK1, Ϫ2, TYK2, STAT1, -2, -3, -4, and -5 in naive CD4 ϩ T cells (3)(4)(5)(6), and enhances proliferation in naive but not memory CD4 ϩ T cells (1). IL-27 also induces expression of T-box expressed in T cells (Tbet), 4 a master transcriptional regulator for Th1 differentiation (7), and subsequent IL-12R␤2, but down-regulates expression of a Th2-specific transcriptional factor, GATA3, and synergizes with IL-12 in primary IFN-␥ production (1,3,4,6).…”
Section: Stat3 Is Indispensable To Il-27-mediated Cell Proliferation mentioning
confidence: 99%
“…IL-27 also promotes the production of IL-10 by various effector CD4 + T cell populations, including Th1 and Th2 cells and CD4 + T cells polarized under Th17-inducing conditions (20)(21)(22)(23)(24)(25). In line with these disparate roles, IL-27 signaling is essential for the generation of early protective T cell responses during Leishmania major (9) and bacillus Calmette-Guérin (8) infections but is required for the suppression of Th1-and Th17-mediated inflammation during Toxoplasma gondii, Trypanosoma cruzi, Mycobacterium tuberculosis, Leishmania donovani, and nonhealing L. major infections (17,(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%